2012
DOI: 10.1111/j.1365-2133.2012.10894.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-B*58:01 allele and severe cutaneous adverse reactions with allopurinol in Han Chinese in Hong Kong

Abstract: This study confirmed the strong association between the HLA-B*58:01 and allopurinol-induced SCAR in Hong Kong Han Chinese patients. A screening test for the HLA-B*58:01 allele should effectively reduce the risk for allopurinol-induced SCAR in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 34 publications
1
63
0
1
Order By: Relevance
“…49 The proportion of males included in studies also varied by study. Most studies reported that the majority of patients were male, with males being a minority in only three studies 48,49,61 For studies that included a control group, 13,14,47,48,51,[53][54][55]59,68,70 the proportion of males was well balanced in both arms in only two. 13,68 The majority of studies had a greater proportion of males in the control group 48,51,[53][54][55]59,70 than the allopurinol group.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 The proportion of males included in studies also varied by study. Most studies reported that the majority of patients were male, with males being a minority in only three studies 48,49,61 For studies that included a control group, 13,14,47,48,51,[53][54][55]59,68,70 the proportion of males was well balanced in both arms in only two. 13,68 The majority of studies had a greater proportion of males in the control group 48,51,[53][54][55]59,70 than the allopurinol group.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Most studies reported that the majority of patients were male, with males being a minority in only three studies 48,49,61 For studies that included a control group, 13,14,47,48,51,[53][54][55]59,68,70 the proportion of males was well balanced in both arms in only two. 13,68 The majority of studies had a greater proportion of males in the control group 48,51,[53][54][55]59,70 than the allopurinol group. 14,47 Thirteen studies [50][51][52][53][54][55][56]58,61,63,[68][69][70] explicitly reported the ethnicity of their subjects, although the ethnicity is implied (to be European) in another.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across studies thus far, all Han Chinese patients with allopurinol-induced SJS were found to be HLA-B*5801-positive 3,7,9 (Table 2). However, HLA-B*5801 has a 20% carriage rate in Han Chinese 3 , meaning 1 in 5 Han Chinese patients starting allopurinol would be denied it if primary screening were applied.…”
Section: To the Editormentioning
confidence: 99%
“…A multinational study reported that allopurinol is the most common drug associated with SJS and toxic epidermal necrolysis 2 . Genomic studies have shown that the HLA-B*5801 allele is a strong risk factor (OR 34-348) for developing allopurinol-induced SJS 3,4,5,6,7,8 . However, the clinical utility of HLA-B*5801 is unclear.…”
Section: To the Editormentioning
confidence: 99%